A Note on Reporting of Reservoir C-14 Disequilibria and Age Offsets - Soulet, Guillaume; Skinner, Luke C.; Beaupré, Steven R.; Galy, Valier (RADIOCARBON, 2016)
Reservoir age offsets are widely used to correct marine and speleothem radiocarbon age measurements for various calibration purposes. They also serve as a powerful tracer for carbon cycle dynamics. However, a clear terminology regarding reservoir age offsets is lacking, sometimes leading to miscalculations. This note seeks to provide consistent conventions for reporting reservoir C-14 disequilibria useful to a broad range of environmental sciences. This contribution introduces the (FR)-R-14 and R-14 metrics to express the relative C-14 disequilibrium between two contemporaneous reservoirs and the R metric as the associated reservoir age offset.
Keywords: freshwater effect; hardwater effect; radiocarbon; Reservoir age; Reservoir effect; ventilation age